Optimal use of linkage disequilibrium, haplotypes, and integrated maps for positional cloning - Morton, Newton; Collins, Andrew (Henry Stewart Talks, 2004)
The use of LD for localization of disease genes, The evolutionary theory behind LD maps, Comparison of alternative metrics and genetic models, Effect of SNP selection on power, Extension to haplotype analysis, The utility of maps that integrate physical, linkage and LD data
Archived at 2021/02/25